Screening of antibacterial activity of some underutilized fruits of Sapotaceae - Patel, P. R. (2017)
Screening of underutilized fruits of Sapotaceae family Manilkara hexandra and Mimusops elengi were examined for antibacterial activity at their successive stages of growth and ripening. Zone of inhibition and minimum inhibitory concentration (MIC) were determined against medically important bacterial strains namely Bacillus cereus, Bacillus subtilis, Micrococcus luteus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, Salmonella paratyphi and Salmonella typhi. The infusion extracts were used and the zone of inhibition was determined by agar well diffusion method. The methanol extracts of both the fruits screened for the present study proved to be more potent than the other extracts used. The pre-ripened and ripened stages of both the fruits exhibited moderate to high activity against most of the tested organisms. Higher activity was recorded using the fruit extracts of Manilkara hexandra while Mimusops elengi exhibited less activity against most of the tested bacterial strains. MIC value of 1 mg/ml was found effective while using methanol extract of ripened fruit of Mimusops elengi against Salmonella typhi and methanol extract of ripened fruit of Manilkara hexandra at 2 mg/ml inhibited Salmonella paratyphi and Salmonella typhi. Hence, the present study concludes that the underutilized fruits of Manilkara hexandra and Mimusops elengi can be further studied to discover the bioactive natural compounds that may serve and facilitate pharmacological studies leading to synthesis of a more potent drug with reduced toxicity.